Facing complications of direct anterior approach in total hip arthroplasty during the learning curve - Dall’Oca, Carlo (Acta Biomed, 2020)
BACKGROUND: This study aims to evaluate complications and early postoperative clinical outcomes of direct anterior approach (DAA) in total hip arthroplasty (THA). METHODS: Ninety-one consecutive patients who underwent primary elective unilateral THA between January 2013 and December 2019 were identified. Collected data included age of patient, BMI, ASA score, EBL (estimated blood loss), LOS (length of stay), operating time, and intra/postoperative complications. The recorded complications included prolonged wound drainage without infection, superficial and deep infection, dislocation, periprosthetic fracture, aseptic loosening or failure of osteointegration and nervous damage. Any reoperation, with or without prosthetic component revision, was recorded. RESULTS: Fourteen complications (15,4%) and 12 (13,18%) postoperative anemizations were observed in this series. No deep infection was reported. Most common complications were nerve damage (3/91; 3,29%), greater trochanter fracture (3/91; 3,29%), and wound trouble (3/91; 3,29%). Two (2,19%) dislocations were reported. One (1,09%) intraoperative periprosthetic fracture was treated with cerclage wiring. One (1,09%) revision was needed for an acetabular mobilization. One patient (1,09%) had severe periprosthetic ectopic ossifications (Brooker 4), needing reintervention because of severe limitations of the range of motion (ROM). CONCLUSIONS: Complications rate in this study with THA by DAA is comparable to those reported in literature. DAA is a safe, efficient procedure but it needs a steep learning curve. (www.actabiomedica.it)